2019
DOI: 10.1093/eurpub/ckz186.416
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Midwifery Education System in Armenia

Abstract: Background Competencies, knowledge and skills of health care professionals largely depend upon their education. Well-educated and competent midwives can improve women’s and infants’ health related outcomes. The current study evaluated the compliance of the current midwifery education system in Armenia with the global International Confederation of Midwives (ICM) standards. Methods The research team used a qualitative cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These 64 documents described the qualifications to practice midwifery from 35 countries ( Table 1 ). The majority of the included information was from midwifery governing body web pages ( n = 11) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and law documents ( n = 11) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] followed by midwifery assessment reports ( n = 10) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and midwifery association web pages ( n = 8) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The rest of the documents were from published articles ( n = 7) [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], government web pages ( n = 7) [ 74 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 64 documents described the qualifications to practice midwifery from 35 countries ( Table 1 ). The majority of the included information was from midwifery governing body web pages ( n = 11) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and law documents ( n = 11) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] followed by midwifery assessment reports ( n = 10) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and midwifery association web pages ( n = 8) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The rest of the documents were from published articles ( n = 7) [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], government web pages ( n = 7) [ 74 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Among the included countries with complete information on study duration ( n = 21), it was observed that most direct-entry degrees ( n = 10) [ 31 , 33 , 53 , 54 , 60 , 61 , 67 , 69 , 70 , 75 , 84 , 87 , 91 ] or diplomas ( n = 3) [ 41 , 44 , 56 ] in midwifery were three- or four-year-long courses, whereas post-nursing ( n = 3) [ 39 , 50 , 51 , 52 , 57 , 59 ] or postgraduate ( n = 2) [ 49 , 68 ] midwifery qualifications required between seven months to two years of study ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%